Rule Extraction from Active Contour Classifiers - Szczepaniak, Piotr S.; Pierścieniewski, Łukasz (Wydawnictwo Politechniki Łódzkiej, 2018)
In this paper, the idea of rule extraciton from active contour classifiers is presented. The concepts are new in relation to active contour approach. The problem is illustrated by examples having roots in technical diagnosis and in analysis of content of images.
Keywords: active contour approach; rule extraction; classification; decompositional rule extraction; aktywne podejście do konturu; ekstrakcja reguł; klasyfikacja; ekstrakcja reguł dekompozycji